(3eZGfj GdhaG HeYGfj GdGcJaG(B((3ddcdGYj(B)s - (3eMeO Hf YHO GdSdGe Hf MeOhf GdHfGfj GdeGdcjs; (3GdcdGYj , SdjeGf Hf ehSi Hf SGde Hf MSGf GdMejQj, CHh GdQHjY,J (B634 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi GNJGQ eMeOkG Udi Gddg Ydjg hSde Ydi SGFQ GdCfHjGA hGdeQSdjf bHd Cf jchfhG ai GdCUdGH fWakG s
(3BNQgG (B:s
(3hHYO ehJ CHjg hgh ebje HTNU jbGd dg QHjYg Hf NQGY Ch NRGY Hf QHjYI GdZOQ s
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B136 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B399s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B686 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B405 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs